Antarctic contribution to sea level rise observed by GRACE with improved GIA correction - Ivins, E.R. (author); James, T.S. (author); Wahr, J. (author); Schrama, E.J.O. (author); Landerer, F.W. (author); Simon, K.M. (author) (Journal of Geophysical Research: Solid Earth, 2013)
Antarctic volume changes during the past 21 thousand years are smaller than previously thought, and here we construct an ice sheet history that drives a forward model prediction of the glacial isostatic adjustment (GIA) gravity signal. The new model, in turn, should give predictions that are constrained with recent uplift data. The impact of the GIA signal on a Gravity Recovery and Climate Experiment (GRACE) Antarctic mass balance estimate depends on the specific GRACE analysis method used. For the method described in this paper, the GIA contribution to the apparent surface mass change is re-evaluated to be +55±13 Gt/yr by considering a revised ice history model and a parameter search for vertical motion predictions that best fit the GPS observations at 18 high-quality stations. Although the GIA model spans a range of possible Earth rheological structure values, the data are not yet sufficient for solving for a preferred value of upper and lower mantle viscosity nor for a preferred lithospheric thickness. GRACE monthly solutions from the Center for Space Research Release 04 (CSR-RL04) release time series from January 2003 to the beginning of January 2012, uncorrected for GIA, yield an ice mass rate of +2.9± 29 Gt/yr. The new GIA correction increases the solved-for ice mass imbalance of Antarctica to ?57±34 Gt/yr. The revised GIA correction is smaller than past GRACE estimates by about 50 to 90 Gt/yr. The new upper bound to the sea level rise from the Antarctic ice sheet, averaged over the time span 2003.0–2012.0, is about 0.16±0.09 mm/yr. Space Engineering Aerospace Engineering